أثر استخدام تطبيق الواتس آب WhatsApp والكتابة لدى طلبة اللغة العربية في الصف الحادي عشر في محافظة مسقط واتجاهاتهم نحو استخدامه في تنمية مهارتي القراءة إعداد، عبد المطلب بن شرف بن علي الموسوي - موسوي، عبد المطلب شرف علي
In the context of seeking to employ technology in the educational process and finding technical solutions to develop reading and writing skills and attitudes, This study aimed to reveal the impact of the use of WhatsApp in the eleventh grade in Muscat province while performing educational activities in the Al-Mu'nis course (one of the Arabic language courses) by explaining the impact of this application on the development of variables (reading skills - writing skills) and trends towards the use of WhatsApp in the development of reading and writing skills. The researcher used the semi-experimental method and the design of the two experimental and control groups (pretest and postest) to verify the validity of the research assumptions. The researcher divided the research sampling into two control and experimental groups, each consisting of (58) students, where educational activities were performed in accordance with the electronic method through the WhatsApp group with students of the experimental group while educational activities were performed with the control group in accordance with the traditional method. The researcher employed the research tools before and after the two groups, which consisted of a tool (literacy skills test) which is from a department specialized in reading skills and a section specialized in writing skills and a tool (measure of directions) which is three dimensions (cognitive dimension - behavioral dimension - and emotional dimension). The results revealed statistically significant differences in favor of the students of the experimental group in the results of the reading and writing skills, and the existence of statistically significant differences in favor of the experimental group in the results of the trend scale.